Future Needs and Challenges in Tribo-Corrosion Research and Testing - Blau, P. J.; Wood, R.; Stack, M. M.; Mischler, S.; Jiang, J.; Drees, D.; Rocha, L. A. [UNESP]; Wimmer, M. A.; Celis, J-P.; Cowan, R.; Celis, J. P. (Astm International, 2013)
Tribo-corrosion is an emerging interdisciplinary subject that spans from basic research on the behavior of surfaces in mechanical contact in chemically active surroundings to the test methods needed to quantify its effects, and from the selection of materials for bio-implants to the minimization of surface degradation and wastage in advanced energy conversion systems. Such a diverse field brings with it many challenges in understanding, testing, standardization, and application to engineering practice. This paper summarizes a panel discussion and participant survey held at the Third International Symposium on Tribo-Corrosion in Atlanta, GA, in Apr. 2012. It reflects a sense of agreement on many of the key scientific challenges in the field and the fact that tribo-corrosion is still in its infancy in terms of broad industry recognition, education, and the ability of those who conduct tribo-corrosion research to connect their laboratory results and theories to applications. Some sub-fields, notably the bio-tribo-corrosion of medical implants, have witnessed active international research efforts, but the engineering community in many other important areas of technology may not yet be aware of the field despite numerous tribo-corrosion problems that may exist within their purview.
Keywords: wear corrosion synergism; tribo-corrosion; wear testing